Upaya Kepala Madrasah dalam Meningkatkan Eksistensi Madrasah Ibtidaiyah Swasta - Japaruddin Japaruddin; Hamengkubuwono Hamengkubuwono; Kusen Kusen; Jumira Warlizasusi; Murni Yanto; Irwan Fathurrochman (Alignment:Journal of Administration and Educational Management, 2020)
This study aims to determine how the efforts of the head of madrasah to improve the existence of Private Madrasah Ibtidaiyah (MIS) 01 Kepahiang. This research uses a qualitative approach with descriptive analysis methods, data collection through techniques, interviews, observation and documentation. The results showed that the efforts made by the head of madrasah were through improving madrasah management so that managing madrasahs went better. To carry out this effort involves all components in the madrasah so that the efforts of the head of the madrasah can be carried out properly. The head of madrasah receives positive support from teachers and the community so that they can develop the existence of the madrasah. The internal supporting factor for the condition of the madrasah is comfort to work so that activities can run well. Then externally the community supports the learning activities. The obstacle is the lack of optimal madrasah activity time, making it difficult to implement management to improve the existence of an effective and efficient madrasah. Keywords: Efforts of the Head of Madrasah, Increasing the Existence of Madrasas.